Pengaruh Penerapan Teori Organisasi terhadap Kinerja Keuangan PT Bayan Resources TBK: Analisis Kuantitatif Berdasarkan Laporan Keuangan Periode Tahun 2022–2024 - Rismawati Rismawati; Dea Dalila; Faisal Dhermawan; Putri Delvina Sari (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of the application of organizational theory on the financial performance of PT Bayan Resources Tbk, with a quantitative approach based on the financial statements for the period 2022 to 2024. The organizational theories tested in this study include contingency theory, organizational structure theory, and leadership theory and organizational culture. Financial performance is measured using financial ratios such as profitability, liquidity, and efficiency ratios. The analysis method used is multiple linear regression analysis to identify the relationship between organizational theory variables and financial performance variables. The results of the study show that the application of organizational theory has a significant influence on improving the company's financial performance, with the main role lying in adaptive organizational structure and effective leadership. These findings provide practical implications for the management of PT Bayan Resources Tbk in formulating organizational strategies to support the improvement of the company's financial performance in the future.